Environmental and techno-economic feasibility study of photovoltaic systems in Northern Bangladesh (Journal of Bangladesh Academy of Sciences, 2025)
The feasibility study for the photovoltaic solar systems in Rajshahi, Bogura, and Sirajganj regarding Bangladesh, comprehensively addresses financial, technical, and environmental factors to attract both the national and international investors. The objective of the analysis is to evaluate photovoltaic (PV) solar systems in northern cities of the Bangladesh; Rajshahi, Bogura, and Sirajganj to minimize the effect of the global warming caused by burning of the fossil fuels as well as to improve region’s sustainable development, which was hampered by the factory pollution. To analyze study and the verify its techno-economic and environmental sustainability, RETScreen Expert and Homer software is utilized. Sensitivity analysis emphasizes importance of the considering the diesel prices, inverter efficiency, and interest rates, as these factors significantly impact cost of energy (COE). Among these zones, Rajshahi attitudes out with lowest total emissions and the carbon dioxide levels, making it the furthermost favorable option for the reducing pollution and advancing the sustainable technology in this region.J. Bangladesh Acad. Sci. 49(2); 189-204: December 2025